Comparative Effect of Atorvastatin and Trigonella foenum graecum L. Seeds in the Postmenopausal Hyperlipidemia - Janki Ketanbhai Desai,; Sateesh Belemkar,; Manish Patel, (International Journal of Phytomedicine, 2015)
Trigonella foenum graecum L. (Fabaceae) seeds have been extensively used in Ayurveda and Unani medicine. It has been used as a traditional medicine for a household remedy against various human ailments. The seeds have been shown to possess hypoglycemic, hypocholesterolaemic and antioxidant activity. The present study is to evaluate whether ovariectomised (OVX) Wistar rats could form an experimental model of postmenopausal hyperlipidemia and to evaluate the antihyperlipidemic potential of Atorvastatin (AT) and Ethyl acetate extract of Trigonella foenum graecum L. Seeds (ET) in OVX Wistar rats and toxicity associated with it. Ovariectomy was performed to mimic the postmenopausal hyperlipidemic condition in Wistar rats. The effects of AT and ET on body weight, weight of uterus and the levels of total cholesterol (TC), triglycerides (TG), high density lipoproteins (HDL), low density lipoproteins (LDL), very low density lipoprotein (VLDL) were also evaluated. The rats in OVX control group showed 51% weight gain when compared with vehicle control group. The serum TC, TG, LDL, VLDL of OVX control group was found to be increased significantly; serum HDL level was reduced and atrophy of uterus was observed in comparison with vehicle control group. The ET showed the significant (P<0.05, P<0.01) antihyperlipidemic potency when compared with AT & proportional antihyperlipidemic potency in comparison with Estradiol benzoate (EB). These findings confirm the bilateral OVX Wistar rats as a model of postmenopausal hypercholesterolemia. The significant antihyperlipidemic activity of ET thus lends pharmacological credence to the suggested use of the plant as a safe natural remedy in the treatment of postmenopausal hyperlipidemia.